A Multicenter Analysis of Subjectivity of Indirect Immunofluorescence Test in Antinuclear Antibody Screening - Vildan TURAN FARAŞAT; Talat ECEMİŞ and Yavuz DOĞAN and Aslı Gamze ŞENER and Gülfem TEREK ECE and Pınar Erbay DÜNDAR and Tamer ŞANLIDAĞ (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the interpretation of the antinuclear antibody (ANA)-indirect immunofluorescence (IIF) test results based on the interpreter-related subjectivity and to examine the inter-center agreement rates with the performance of each laboratory. Patients and methods: The ANA-IIF testing was carried out in a total of 600 sera and evaluated by four laboratories. The inter-center agreement rates were detected. The same results given by the four centers were accepted as gold standard and the predictive values of each center were calculated. Results: The inter-center agreement was reported for ANA-IIF test results from 392 of 600 (65.3%) sera, while 154 of 392 results were positive. Four study centers reported 213 (35.5%), 222 (37.0%), 266 (44.3%), and 361 (60.2%) positive test results, respectively. In terms of the patterns, the highest and lowest positive predictive values were 72.3% and 42.7%, respectively, while the highest and lowest negative predictive values were 99.6% and 61.5%, respectively. The agreement for semi-quantitative evaluation at three levels of fluorescence intensity stated by four centers was detected in 100 sera at 87% 3(+), while the other two levels were 6% and 7%. The highest predictive value for the highest fluorescence intensity of 3(+) was found to be 71.9%. Conclusion: Significant differences may be observed among laboratories in terms of qualitative results, patterns, and semi-quantitative determination of the fluorescence intensity in the ANA-IIF testing, particularly at low fluorescence intensity levels and in those with speckled patterns. In case of any discrepancy between ANA-IIF test and clinical prediagnosis, the test should be repeated in another laboratory, if necessary.